Chemical composition and antioxidant activity of essential oils of three endemic medicinal plants of Iran (Bangladesh Journal of Botany, 2014)
Hydro-distillated essential oils (EO) antioxidant activity of three endemic medicinal plants of Iran namely, Heracleum lasiopetalum Boiss., Kelussia odoratissima Mozaff., and Ferulago angulata (Schlecht.) Boiss were studied. The results indicated that the major components of the EOs were 2-ethylhexyl acetate (34.5%), n-octanol (6.5%), and hexanol (5.1%) for H. lasiopetalum fruits; Z-?-ocimene (20.5), ?-pinene (11.6%), and ?-phellandrene (9.3) for F. angulata aerial parts; ?-pinene (20.1%), 1,8-cineole (18.2%), and Zligustilide (15.5%) for K. odoratissima aerial parts. The three EOs having high antioxidant activity could be used as an alternative preservative instead of synthetic ones in food industry. DOI: http://dx.doi.org/10.3329/bjb.v42i2.18038 Bangladesh J. Bot. 42(2): 327-332, 2013 (December)